Enhanced alcohol self-administration and reinstatement in a highly impulsive, inattentive recombinant inbred mouse strain - Loos, Maarten; Staal, Jorn; Smit, August B.; De Vries, Taco J.; Spijker, Sabine (Frontiers in Behavioral Neuroscience, 2013)
Deficits in executive control have frequently been associated with alcohol use disorder. Here we investigated to what extent pre-existing genetically encoded levels of impulsive/inattentive behavior associate with motivation to take alcohol and vulnerability to cue-induced reinstatement of alcohol seeking in an operant self-administration paradigm. We took advantage of BXD16, a recombinant inbred strain previously shown to have enhanced impulsivity and poor attentional control. We compared BXD16 with C57BL/6J mice in a simple choice reaction time task (SCRTT) and confirmed its impulsive/inattentive phenotype. BXD16 mice were less active in a novel open field, and were equally active in an automated home cage environment, showing that increased impulsive responding of BXD16 mice could not be explained by enhanced general activity compared to C57BL/6J mice. After training in a sucrose/alcohol fading self-administration procedure, BXD16 showed increased motivation to earn 10% alcohol solution, both under fixed ratio (FR1) and progressive ratio (PR2) schedules of reinforcement. Responding on the active lever readily decreased during extinction training with no apparent differences between strains. However, upon re-exposure to alcohol-associated cues, alcohol seeking was reinstated to a larger extent in BXD16 than in C57BL/6J mice. Although further studies are needed to determine whether impulsivity/inattention and alcohol seeking depend on common or separate genetic loci, these data show that in mice enhanced impulsivity coincides with increased motivation to take alcohol, as well as relapse vulnerability.